GAYA KEPEMIMPINAN RASUL PAULUS RELEVANSINYA BAGI PEMIMPIN MASA KINI - Yanto Sandy Tjang; Laurentius Prasetyo; Felisitas Yuswanto; Mayong Andreas Acin; Kristianus Atok; Alfeus Sunarso (Jurnal Masalah Pastoral, 2026)
This study aims to analyze the leadership model of the Apostle Paul and its relevance for contemporary leadership amid accelerating transformations across social, political, economic, and technological domains. The current leadership crisis—characterized by moral decline, corruption, and the misuse of authority—underscores the urgent need for a renewed leadership paradigm grounded in spiritual and moral integrity. Within this context, Paul is widely regarded as an archetype of transformative leadership who integrates vision, spirituality, and adaptability in his cross-cultural missionary work. Employing a descriptive qualitative method through a library research approach, this study examines primary and secondary sources, including the Scriptures, theological literature, and scholarly works on Christian leadership. The analysis demonstrates that Paul’s leadership is characterized by five core principles: serving as a divine calling, involving co-workers, nurturing spiritual maturity, delegating ministry according to gifts, and releasing responsibility without abandoning guidance. These principles emphasize collaboration, character formation, and ongoing mentorship, indicating their applicability across contemporary ecclesial and secular leadership contexts. Consequently, Paul’s leadership exemplifies a transformative model rooted in love, integrity, and spiritual responsibility, offering contemporary leaders a paradigm of servant leadership grounded in humility, faithfulness, and moral conviction.